Literal Reading Comprehension Improvement through Texts Containing Idiomatic Expressions among Senior High School Students - Satriani; Herman Resyadi; Arni Arsyad Sultan (Teaching English and Language Learning English Journal, 2025)
This study investigates the improvement of senior high school students’ literal reading comprehension through the use of texts containing idiomatic expressions. The objective of this research is to determine the extent to which idiomatic expression texts can enhance students’ literal comprehension of written materials. A quantitative approach was employed using a pre-experimental design with a one-group pre-test and post-test model. The participants were 20 Grade X students at MA Tinco during the 2023/2024 academic year. The results show that the average pre-test score for literal reading comprehension was 46.70, with a standard deviation of 5.440, a minimum score of 35, and a maximum score of 56. After the intervention, the average post-test score increased to 86.65, with a standard deviation of 7.506, a minimum score of 74, and a maximum score of 98. These findings indicate a significant improvement in students’ literal reading comprehension after being taught using idiomatic expression texts. Hypothesis testing with a paired sample t-test produced a t-value of 17.533, exceeding the critical t-table value of 1.725, with a p-value of 0.000. Since the p-value was less than 0.05, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted. The N-Gain analysis yielded an average score of 74.38, categorizing the intervention as “moderately effective.” Therefore, it can be concluded that the use of texts containing idiomatic expressions is moderately effective in improving the literal reading comprehension of Grade X students at MA Tinco.